2018
DOI: 10.1016/j.compind.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Return on investment from the use of product configuration systems – A case study

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…utilitarian, uniqueness, and self-expressiveness benefits) [2,60,61]. Sales of customized products via OSCs, and more generally via configurators, also help mass customizers [62]. Consequently, OSCs, and more generally, product configurators, are also considered as key enablers for MC implementation [63].…”
Section: Online Sales Configuratorsmentioning
confidence: 99%
“…utilitarian, uniqueness, and self-expressiveness benefits) [2,60,61]. Sales of customized products via OSCs, and more generally via configurators, also help mass customizers [62]. Consequently, OSCs, and more generally, product configurators, are also considered as key enablers for MC implementation [63].…”
Section: Online Sales Configuratorsmentioning
confidence: 99%
“…Dentre os inputs utilizado estavam: localização, número de lojas, projeção de demanda e investimento de cada loja. Kristjansdottir et al (2018) analisaram o papel dos sistemas operacionais de produção das companhias sobre a redução do consumo de recursos produtivos, dentre eles a redução do tempo de fabricação, aumento da qualidade dos produtos e aumento das vendas. Em suma, os autores analisaram, por meio de um estudo de caso em uma empresa multinacional de produção de bombas, como que o sistema operacional de produção, que fornece suporte desde o processo produtivo até o processo da venda, pode afetar positivamente o retorno sobre os investimentos (ROI) realizado pela companhia.…”
Section: Retorno Sobre O Investimento (Roi)unclassified
“…PCSs are a proven concept that add significant value for companies with complex configurable products. Though the decision to implement a PCS comes with the expected costs of software, training, etc., studies have shown that their return on investment (ROI) is very high [18]. The success of information systems and technology increases organizational performance and reduces overall costs [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of this analysis indicate that even though the cost of maintaining a system can be relatively high, the economic and business benefits can justify the need. In terms of PCSs, this can be argued by considering studies on the ROI of such investments [18]. The ROI calculation includes the cost of maintaining a PCS, and the savings are still significant (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation